Consumer behaviour towards online payment system with special reference to Gorakhpur city - Tripathi, Santosh Kumar (International journal of economic perspectives, 2007)
Technology has come to play a significant role in the where as of development of newer modes of payment and settlement. Today this end, innovative products such as e-banking and e-payments have been introduced. Internet banking has been the predominant mode of e-banking in India with the internet offering itself as a new delivery mechanism for the banks in reaching the customer. Online payment was very much used in recent years due to convenience, speedy transactions, saving time, attractive sales promotional offers, etc, Despite these factors, there were various transactional and non- transactional issues involved such as internet user being uncomfortable often etc. which act as deterrents. However, the future for online payment looks bright and promising. This was especially true in the context of consumers in small cities, where online payment was still new, and consumers were less familiar and often more skeptical towards it.